2017
DOI: 10.1208/s12249-017-0779-0
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Needle-free Injection System: Comparison to 1 ml Standard Subcutaneous Injection

Abstract: A needle-free delivery system may lead to improved satisfaction and compliance, as well as reduced anxiety among patients requiring frequent or ongoing injections. This report describes a first-in-man assessment comparing Portal Instruments' innovative needle-free injection system with subcutaneous injections using a 27G needle. Forty healthy volunteer participants each received a total of four injections of 1.0 mL sterile saline solution, two with a standard subcutaneous injection using a 27G needle, and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This approach allows for real time control over the jet speed ejected from the device, and means that a single device can be used to target different depths, volumes, or adjusted between different patients. Motor driven jet injectors have only recently been developed to deliver up to 1 mL per injection, a volume comparable to that of spring or gas driven devices [34], [35]. Our results show that a motor driven injector enables dental anaesthetic delivery, even when presented with the additional resistance provided by the thin, tubular attachment.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This approach allows for real time control over the jet speed ejected from the device, and means that a single device can be used to target different depths, volumes, or adjusted between different patients. Motor driven jet injectors have only recently been developed to deliver up to 1 mL per injection, a volume comparable to that of spring or gas driven devices [34], [35]. Our results show that a motor driven injector enables dental anaesthetic delivery, even when presented with the additional resistance provided by the thin, tubular attachment.…”
Section: Discussionmentioning
confidence: 74%
“…The device presented here has a maximum volume of 0.3 mL so would require two injections to achieve an infiltration. Changes to the ampoule or motor used in our device could be made to accommodate sufficient volume to allow an infiltration to be performed in a single dose [34], [35], [37]. While it would be preferable to have the option of performing an infiltration in a single injection, it is likely that delivery over multiple injections may be beneficial for maximising patient comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Jet injection has a low technical threshold yet the injection powers in existing products are static, with only a few exceptions. Nikola et al reported depth-controllable computer-regulated injection and Miyazaki et al proposed a PJI device with an adaptable injection depth [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, combinatorial strategies involving jet injection followed by EP have been examined for use in efficient DNA vaccine delivery [1214]. More recently, a sophisticated new type of needleless device was reported to control the injection depth and speed using a computer-controlled motor system and an electrical feedback system; however, there has yet to be reports on its application for DNA vaccination [15]. Thus, the development of novel DNA vaccines requires testing of new devices specific for intradermal DNA vaccination on experimental animal models.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of needles within the delivery device can result in pain during administration, although there has been an improvement in delivery devices with much finer needles (30 G) being routinely used to reduce pain. Modern technologies could completely obviate needles, using instead a needle-free system to deliver a payload of the drug with less associated pain [ 207 ]. The SC tissue limits injection volume to approximately 2.0 mL.…”
Section: Polypeptide Deliverymentioning
confidence: 99%